2020
DOI: 10.1038/s41467-020-19779-6
|View full text |Cite
|
Sign up to set email alerts
|

Controlling bimerons as skyrmion analogues by ferroelectric polarization in 2D van der Waals multiferroic heterostructures

Abstract: Atom-thick van der Waals heterostructures with nontrivial physical properties tunable via the magnetoelectric coupling effect are highly desirable for the future advance of multiferroic devices. In this work on LaCl/In2Se3 heterostructure consisting of a 2D ferromagnetic layer and a 2D ferroelectric layer, reversible switch of the easy axis and the Curie temperature of the magnetic LaCl layer has been enabled by switching of ferroelectric polarization in In2Se3. More importantly, magnetic skyrmions in the bime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 67 publications
(78 reference statements)
2
63
0
Order By: Relevance
“…Utilizing an outofplane electric polarization of a 2D fer roelectrics, instead of a tunneling current, to write and erase skyrmion may reduce energy dissipation in skyrmionbased devices. [33,34] To realize such ferroelectric control, we attach a CuInP 2 S 6 monolayer to the WTe 2 /CrCl 3 HS. The ferroelectric polarization of CuInP 2 S 6 can be switched by the application of an electric field, as shown in Figure 6a.…”
Section: Nonvolatile-ferroelectric-polarization-controlled Magnetic Skyrmionmentioning
confidence: 99%
“…Utilizing an outofplane electric polarization of a 2D fer roelectrics, instead of a tunneling current, to write and erase skyrmion may reduce energy dissipation in skyrmionbased devices. [33,34] To realize such ferroelectric control, we attach a CuInP 2 S 6 monolayer to the WTe 2 /CrCl 3 HS. The ferroelectric polarization of CuInP 2 S 6 can be switched by the application of an electric field, as shown in Figure 6a.…”
Section: Nonvolatile-ferroelectric-polarization-controlled Magnetic Skyrmionmentioning
confidence: 99%
“…[462] A recent experiment demonstrated that the magnetic skyrmions can also exist in the form of bimerons in the vdW LaCl/In2Se3 heterostructure and can be manipulated by switching the polarization in In2Se3 using electric fields. [463] Owing to the low Curie temperatures of the so far investigated 2D magnetic materials, skyrmion systems can only be stabilized at low temperatures thus far, limiting the practical applications of these systems. Therefore, further efforts to stabilize skyrmions in 2D magnetic materials at room temperature without an external applied magnetic field and their efficient manipulation under external electric fields are desired.…”
Section: Skyrmionsmentioning
confidence: 99%
“…It is noteworthy that most known 2D magnets, no matter experimentally verified or theoretical predicted, are based on spin moments of 3d electrons, whose orbitals are spatially localized with strong Hubbard correlation [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Apart from these transition metal compounds with unpaired 3d electrons, rare earth compounds with unpaired 4f electrons also play a significant role in modern magnets.…”
Section: Introductionmentioning
confidence: 99%